Carotid artery intima-media thickness in women with polycystic ovary syndrome: A cross-sectional study - Nazanin Farshchian; Parisa Bahrami Kamangar; Mohammad Reza Ghasempour (International Journal of Reproductive BioMedicine)
Abstract Background: Obesity in polycystic ovary syndrome (PCOS) may increase the risk of cardiovascular disease. Carotid intima-media thickness (CIMT) is an acceptable marker in assessing the risk of heart disease. Objective: This study aimed to evaluate the CIMT in PCOS women compared to non-PCOS women. Materials and Methods: This cross-sectional study was conducted on 48 women who referred to Imam Reza hospital, Kermanshah, Iran from July 2020–2021. Women were divided into 2 groups of PCOS and non-PCOS women (n = 24/each). The intima-media thickness of participants' carotid artery was measured on both sides in 3 areas, and its mean was recorded. Results: The mean thickness of the carotid artery intima-media in the case group was within the normal range; but it was significantly higher than the control group (0.71 ± 0.17 vs. 0.57 ± 0.09 mm, p = 0.019). Conclusion: Considering the higher thickness of CIMT in women with PCOS, it can be concluded that PCOS increases the risk of heart diseases in women.